Assessment of Reamer Irrigator Aspirator System (RIA) filtrate for its osteoinductive potential in a validated animal model. Issue 6 (June 2018) - Wessel, Alex R.; Crist, Brett D.; Stannard, James P.; Della Rocca, Gregory J.; Stoker, Aaron M.; Bozynski, Chantelle C.; Cook, Cristi R.; Kuroki, Keiichi; Ahner, Carin E.; Cook, James L.
Abstract: Purpose: Previous studies indicate that Reamer Irrigator Aspirator (RIA) filtrate contains proteins that have the potential to stimulate bone healing. This study aimed to determine the osteoinductive capabilities of RIA filtrate in a validated in vivo model. Methods: With Institutional Review Board approval, RIA filtrates from 9 patients were collected. The filtrate was processed to remove cells and inorganic particles. A portion of each sample was set aside for protein analysis while the remainder was lyophilized and prepared for implantation. With Animal Care and Use Committee approval, athymic mice (n = 16; 32 hind limbs) were randomly assigned to 1 of 4 groups (n = 8 limbs per group) for percutaneous gastrocnemius muscle injection of demineralized bone matrix (DBM) (10 mg), lyophilized RIA powder (10 mg), RIA liquid (10 mg of lyophilized RIA powder in 100ul phosphate buffered saline (PBS)), or DBM (10 mg) + RIA liquid (10 mg in 100ul PBS). Radiographs were obtained 2, 4, and 8 weeks after injection. At 8 weeks, mice were sacrificed and the entire gastrocnemius muscle from each hind limb was collected and processed for histologic examination. Histological sections and radiographs were assessed for ossification/calcification. Data were compared for statistically significant (p < 0.05) differences among groups and strong (R > 0.7) correlations between outcome measures. Results: The protein composition of RIA filtrates was consistent among patients and matched previous data. For all groups, radiographic scores were significantly (p < 0.014) higher (more calcification/ossification) at 8 weeks compared to 2 weeks. Radiographic scores for the DBM and DBM + RIA liquid groups were significantly higher than RIA liquid and RIA powder at 4 weeks and 8 weeks (p < 0.019 and p < 0.049, respectively). Histologic scores were significantly (p = 0.004) higher in the DBM + RIA liquid group compared to the RIA liquid group at 8 weeks. Histologic scores showed strong correlations (r > 0.77) to radiographic scores for all groups. Conclusion: RIA filtrate liquid and powder were osteoinductive in vivo with new bone formation being most abundant using a combination of DBM and RIA filtrate in this validated animal model. RIA filtrate has potential for clinical use in augmenting bone healing treatments.